PERAN PENDAYAGUNAAN ZAKAT PRODUKTIF TERHADAP KESEJAHTERAAN MASYARAKAT DALAM PELAKSANAAN TUJUAN PROGRAM PEMBANGUNAN BERKELANJUTAN (STUDI KASUS BAZNAS PROVINSI SUMATERA UTARA) - Noico Aldiano; Yenni Samri J Nasution; Muhammad Lathief lhamy Nasution (Universitas Islam Negeri Sumatera Utara, 2021)
This study aims to determine how the role of sustainable development programs in alleviating poverty and the role of productive zakat utilization in poverty alleviation and its relationship in achieving the goals of sustainable development programs. Therefore this study uses descriptive qualitative research methodology. Data and facts were collected by means of interviews, observation and documentation. North Sumatra BAZNAS collection uses two programs, namely the zakat collection program and the infaq / shodaqoh collection program. The results of the research show that the assistance provided to mustahik has not been able to fully reduce the poverty rate in Medan City, but it can provide quite good benefits and can reduce the burden on the life of the mustahik. Therefore, zakat can be said to be an instrument that has a strategic role and contribution to achieving sustainable development programs.